Should Carbohydrate Intake Be More Liberal during Oral and Enteral Nutrition in Type 2 Diabetic Patients? - Sobotka, Ondrej; Ticha, Marie; Kubickova, Marketa; Adamek, Petr; Polakova, Lenka; Mezera, Vojtech; Sobotka, Lubos (Nutrients, 2023)
Carbohydrate (CHO) intake in oral and enteral nutrition is regularly reduced in nutritional support of older patients due to the high prevalence of diabetes (usually type 2-T2DM) in this age group. However, CHO shortage can lead to the lack of building blocks necessary for tissue regeneration and other anabolic processes. Moreover, low CHO intake decreases CHO oxidation and can increase insulin resistance. The aim of our current study was to determine the extent to which an increased intake of a rapidly digestible carbohydrate-maltodextrin-affects blood glucose levels monitored continuously for one week in patients with and without T2DM. Twenty-one patients (14 T2DM and seven without diabetes) were studied for two weeks. During the first week, patients with T2DM received standard diabetic nutrition (250 g CHO per day) and patients without diabetes received a standard diet (350 g of CHO per day). During the second week, the daily CHO intake was increased to 400 in T2DM and 500 g in nondiabetic patients by addition of 150 g maltodextrin divided into three equal doses of 50 g and given immediately after the main meal. Plasma glucose level was monitored continually with the help of a subcutaneous sensor during both weeks. The increased CHO intake led to transient postprandial increase of glucose levels in T2DM patients. This rise was more manifest during the first three days of CHO intake, and then the postprandial peak hyperglycemia was blunted. During the night's fasting period, the glucose levels were not influenced by maltodextrin. Supplementation of additional CHO did not influence the percentual range of high glucose level and decreased a risk of hypoglycaemia. No change in T2DM treatment was indicated. The results confirm our assumption that increased CHO intake as an alternative to CHO restriction in type 2 diabetic patients during oral and enteral nutritional support is safe.
Keywords: Humans; Dietary Carbohydrates; glucose; lidé; Blood Glucose; hyperglykemie; glucose metabolism; Diabetes Mellitus, Type 2; Hyperglycemia; enteral nutrition; Insulin; insulin resistance; krevní glukóza; Enteral Nutrition; enterální výživa; diabetes mellitus; diabetes mellitus 2. typu; carbohydrate intake; dietní sacharidy; inzulin